Staff perspectives on independence and collaborative practices in the IRIS intervention: an evaluation in Swedish LSS residential homes - Olsson, Sylvia; Loeb, Carina; Dag, Munir (Frontiers in Rehabilitation Sciences, 2025)
Background and purposeIntensive Rehabilitation Coordination (IRIS), is an intensive, health-promoting habilitative intervention designed to prevent, reduce, and compensate for individuals’ support needs while enhancing their independence. The purpose of this study is to explore staff experiences with the IRIS intervention in a municipality's LSS1 residential homes, with a focus on how independence is defined and operationalized and the resulting impact on service delivery.MethodsA qualitative study was conducted in which staff from various LSS residential homes were interviewed. The interviews were structured to examine differences in the interpretation of independence, the strategies used to support service users, and the collaborative nature of the intervention. Participants were asked to describe their approaches to encouraging or supporting independence in daily tasks and their interactions with quality coordinators.ResultsThe analysis revealed a lack of a shared definition of independence among staff, leading to varied approaches in supporting service users. Some staff members actively promoted independence by encouraging service users to perform everyday tasks on their own, while others performed these tasks for the service users due to practical considerations such as convenience and efficiency. Despite these variations, staff reported that service users still have the opportunity to make their own decisions regarding daily activities. Overall, the IRIS intervention was viewed positively, with its collaborative implementation cited as a key strength.DiscussionThe findings suggest that the absence of a unified conceptualization of independence can lead to inconsistent practices in LSS residential homes, potentially affecting the effectiveness of the intervention. The collaborative approach of IRIS, which fosters joint efforts among municipal professionals, appears to be instrumental in understanding and addressing service users’ needs. Future research should focus on establishing a more standardized definition of independence to improve intervention consistency and outcomes for service users.